Rhetoric, religion, and tragic violence: sacred succor and rancor - Oldenburg, Christopher J.; Daniels, Adrienne E. Hacker (Speaking of religion, 2025)
"Sacred words often provide succor, summoned to comfort individual victims and entire communities ravaged by acts of violence. History also demonstrates, however, that religious discourse, like rhetoric itself, functions as a pharmakon-both a remedy and a poison. Religious discourse evoked to incite or justify violence functions as a kind of rancor or intense partisan anger that distorts reality, exacerbates harm, and eschews the accountability of its perpetrators. Moreover, a third function of religious rhetoric synthesizes sacred succor and rancor to express the productive tension of righteous indignation employed by speakers to decry violence and demand social justice. This compendium of both historic and contemporary speeches on the intersecting themes of religion, rhetoric, and violence endeavors to complicate the rhetoric/violence binary by interpolating religion (another foundational and cultural belief inextricably entangled with both rhetoric and violence) into the dialectic"--